Claiming the role of positive psychology in the fight against prejudice. Issue 1 (2nd January 2023) - Sanders, Christopher A.; Rose, Hope; Booker, Jordan A.; King, Laura A.
ABSTRACT: The problem of inequality presents an important opportunity for positive psychology. We review the many ways that marginalization (including stereotyping, prejudice and discrimination) affects the well-being of minoritized people and suggest that positive psychologists turn their attention to the ways their research interests can be harnessed to remedy this situation – by focusing on the links between positive psychological characteristics and experiences as predictors of stereotyping, prejudice, and discrimination among perpetrators (not simply victims) of bias. We review the limited evidence that exists for such links and for the potential for positive psychology interventions to reduce prejudice. We suggest that incorporating prejudice in positive psychological scholarship can help to resolve controversies in the field. Finally, we provide concrete recommendations for future research practice that will address the goal of a positive psychology that promises fulfillment for all people in a diverse world.